Aborsi dan Berbagai Resiko dalam Pandangan Islam - Sri Widiastuti (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Abortion is an attempt to remove a living fetus from a mother's womb through the intervention of other humans by killing it. Abortion is an act that violates human rights. Regarding unwanted pregnancies, mothers who are victims or on the basis of their wishes should not perform abortions because abortion is a prohibited act in the perspective of Islam, especially when there is no medical basis for doing so. The purpose of the writing is to provide in-depth knowledge about abortion and its various risks in the perspective of Islam. This research method is normative legal research, which is research based on legal materials that focus on reading and studying primary and secondary legal materials. Based on the results of the discussion, it can be concluded that abortion can lead to health and mental risks even to the death of the mother, and in the view of Islam abortion is a form of life terminator that occurs in the fetus of a woman, which is usually done before the fetus is formed perfectly or has not been born and still it should not be done. Based on this, it is certainly contrary to Islamic law.